2021
DOI: 10.1136/bmjpo-2021-001195
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 related multisystem inflammatory syndrome in children (MIS-C): a hospital-based prospective cohort study from Kerala, India

Abstract: ObjectivesTo study (1) epidemiological factors, clinical profile and outcomes of COVID-19 related multisystem inflammatory syndrome in children (MIS-C), (2) clinical profile across age groups, (3) medium-term outcomes and (4) parameters associated with disease severity.DesignHospital-based prospective cohort study.SettingTwo tertiary care centres in Kerala, India.ParticipantsDiagnosed patients of MIS-C using the case definition of Centres for Disease Control and Prevention.Statistical analysisPearson χ2 test o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
2
20
0
1
Order By: Relevance
“…We compared the baseline, clinical characteristics, cardiac and investigative parameters of our study with previously published studies from India (Table 4). [11][12][13][14][15][16][17][18] The mean age among these studies ranged from 60 to 90 months with GI symptoms as the predominant presenting manifestation. Details of these studies, including presence of shock, requirement of inotrope infusion, mechanical ventilation, ICU requirement, presence of CAA and LV systolic function and SARS CoV-2 positivity among the patients, have been summarised.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the baseline, clinical characteristics, cardiac and investigative parameters of our study with previously published studies from India (Table 4). [11][12][13][14][15][16][17][18] The mean age among these studies ranged from 60 to 90 months with GI symptoms as the predominant presenting manifestation. Details of these studies, including presence of shock, requirement of inotrope infusion, mechanical ventilation, ICU requirement, presence of CAA and LV systolic function and SARS CoV-2 positivity among the patients, have been summarised.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, SVM and Naïve Bayes algorithms were the best in overall accuracy, while the logistic regression model resulted in the most sensitive results. In clinical studies and systemical reviews, the main biomarkers that are related to severe condition are elevated CRP [ 15 , 16 ], ferritin [ 11 , 15 , 16 , 21 , 25 , 29 , 30 ], BNP [ 15 , 21 ], D-dimer [ 15 , 16 , 31 ], troponin [ 15 , 16 , 21 ] levels, and reduced platelet [ 12 ] and lymphocyte counts [ 15 , 16 , 21 ]. Although it has been shown that various advanced markers such as IL-6, IL-10, IL-17A, and interferon-gamma (IFN-γ) have prognostic value, limited availability is the main obstacle to their widespread use [ 15 , 16 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies found girls to be affected more. 2,3,8,[13][14][15][16][17] Most of the cases recovered. Only 4 (6%) patients died in this study.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,11 However Indian studies have reported mortality rate ranging from 0 to 27.5%. [13][14][15][16][18][19][20] Mortality was higher in children with associated co-morbidities. Two out of four children (50%) died who had co-morbidities.…”
Section: Discussionmentioning
confidence: 99%